Mechanistic studies on the effect of berberine on methicillin-resistant Staphylococcus aureus drug resistance through modulation of wall teichoteic acid - Fangfang Zhou; Xuemei Gu; Ming Lin; Yue Dai; Wei Wang; Zhongbo Xiong; Yanan Li; Mingming Jiang; Lei Wang (Scientific Reports)
Abstract The emergence of methicillin-resistant Staphylococcus aureus (MRSA) as a major public health concern, particularly in hospital- and community-acquired infections, underscores the urgent need for novel antibiotic therapies. In response to this challenge, there has been renewed interest in exploring natural products derived from traditional plant sources as potential alternatives for combating multi-drug resistance. This study reveals the important mechanism by which the natural compound berberine blocks the WTA biosynthesis pathway by targeting and inhibiting the key enzymes TarO, TarS, and TarM for the synthesis of muramic acid (WTA) in MRSA.Specifically, tarO is the first key enzyme in the synthesis of WTA. tarS and tarM are responsible for the glycosylation of WTA. As a result, BBR significantly inhibits the activities of TarO and TarSM, leading to hindered WTA synthesis and causing structural defects in the cell wall. Notably, this effect can specifically restore the sensitivity of MRSA to β-lactam antibiotics (such as Penicillin and Cefazolin). Drug susceptibility tests indicate that tarO and tarSM mutant strains exhibit significantly enhanced sensitivity to oxacillin, methicillin, and cefotaxime. Additionally, the combination antimicrobial assay demonstrated that BBR synergistically enhanced the effects of oxacillin, methicillin, and cefotaxime on both wild-type and mutant strains, and recovered strains. Further experiments constructing deletion and complementation strains confirmed that the sensitizing effect of BBR directly relies on its inhibition of WTA synthesis. In conclusion, this study not only clarifies a new target for BBR to overcome β-lactam antibiotic resistance but also provides a theoretical basis for developing synergistic antimicrobial strategies based on WTA pathway inhibitors.